Susceptibility assessment of a translational rockslide considering the control mechanism and spatial uncertainty of a weak interlayer: Application study in Tiefeng Township, Wanzhou District - Xiao Feng; Yu Wang; Yang Liu; Qingli Liu; Juan Du; Bo Chai (地质科技通报, 2022)
Translational rockslides are an important disaster that endangers the safety of mountain towns. The dip slopes with weak interlayers are the areas prone to translational rockslides. The regional translational rockslide susceptibility assessment should consider the sliding mechanism and spatial distribution uncertainty analysis of the weak interlayer. Taking Tiefeng Town of Wanzhou District as the study area, based on the detailed investigation of the material, structure and spatial distribution of weak interlayers, this paper analysed the evolution mechanism of shale and mudstone developing into sliding surfaces under the action of primary deposition, tectonic deformation and supergene transformation and summarized the deformation and failure mechanism of translational rockslides. Considering the spatial distribution uncertainty of the weak interlayer, a calculation model of the vertical distribution of the weak interlayer and the contribution of the weak interlayer to slip control in the effective control depth are proposed. The key factors that characterize the sliding structure, including the type of weak interlayer and the contribution degree of the weak interlayer, are selected as susceptibility assessment factors. In addition, four elements, topography, slope structure, hydrogeology and human activities, are considered. The susceptibility of translational rockslides in the study area was assessed with slope units adopting the analytic hierarchy process. The investigation and assessment results show that the mud interlayers of the Jurassic Zhenzhuchong Formation and the shale layer of the Ziliujing Formation are the main potential slip surfaces of the translational rockslide in the study area. The extremely high susceptibility area and high susceptibility area accounted for 9.7% and 25.8%, respectively. The distribution of the underlying weak interlayer and the excavation of the slope units are the main factors affecting the susceptibility to landslide disasters. Human activities such as house building and road excavation are the main triggering factors of translational rockslides.Compared with the susceptibility assessment results without considering the factors of the weak interlayer, the results of the method proposed in this paper are more consistent with the facts.